OPTIMALISASI UMKM SEBAGAI UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT DI RT 14 KELURAHAN KARIANGAU - Yudi Kurniawan; Patria Rahmawati; Elisabeth Milaningrum; Zulkifli; Endang Sri Apriani (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Entrepreneurship through Micro, Small and Medium Enterprises (UMKM) is expected to increase the creativity and ability of the community in channeling their ideas and creations by utilizing available natural resources. The problem of the low level of the community’s economy causes the purchasing power of the people to also decrease, so that it will also have an impact on the welfare and level of education of the community. Therefore, in this Village Development program, our team carried out a coaching program in the form of seminars/socialization about the importance of being an independent income earner for mothers in RT 14, providing assistance in the form of capital equipment and materials to run UMKM intestine chips, providing classroom training basic English for children and fire fighting training.